Exercise training alters lipoprotein particles independent of brown adipose tissue metabolic activity - Motiani, P. (Obes Sci Pract, 2019)
INTRODUCTION: New strategies for weight loss and weight maintenance in humans are needed. Human brown adipose tissue (BAT) can stimulate energy expenditure and may be a potential therapeutic target for obesity and type 2 diabetes. However, whether exercise training is an efficient stimulus to activate and recruit BAT remains to be explored. This study aimed to evaluate whether regular exercise training affects cold‐stimulated BAT metabolism and, if so, whether this was associated with changes in plasma metabolites. METHODS: Healthy sedentary men (n = 11; aged 31 [SD 7] years; body mass index 23 [0.9] kg m(−2); VO(2 max) 39 [7.6] mL min(−1) kg(−1)) participated in a 6‐week exercise training intervention. Fasting BAT and neck muscle glucose uptake (GU) were measured using quantitative [(18)F]fluorodeoxyglucose positron emission tomography–magnetic resonance imaging three times: (1) before training at room temperature and (2) before and (3) after the training period during cold stimulation. Cervico‐thoracic BAT mass was measured using MRI signal fat fraction maps. Plasma metabolites were analysed using nuclear magnetic resonance spectroscopy. RESULTS: Cold exposure increased supraclavicular BAT GU by threefold (p < 0.001), energy expenditure by 59% (p < 0.001) and plasma fatty acids (p < 0.01). Exercise training had no effect on cold‐induced GU in BAT or neck muscles. Training increased aerobic capacity (p = 0.01) and decreased visceral fat (p = 0.02) and cervico‐thoracic BAT mass (p = 0.003). Additionally, training decreased very low‐density lipoprotein particle size (p = 0.04), triglycerides within chylomicrons (p = 0.04) and small high‐density lipoprotein (p = 0.04). CONCLUSIONS: Although exercise training plays an important role for metabolic health, its beneficial effects on whole body metabolism through physiological adaptations seem to be independent of BAT activation in young, sedentary men.